Pengaruh Strategi Diversifikasi terhadap Efisiensi pada Perusahaan Manufaktur yang Tercatat di Bursa Efek Indonesia - Anthony Halim; Claresta Hartawan Setio; Titin Pranoto; Vania Pradipta Gunawan (Studi Akuntansi dan Keuangan Indonesia, 2020)
The purpose of this research is to examine the impact of Related Diversification, Unrelated Diversification and International Diversification on firm’s Efficiency. Related Diversification and Unrelated Diversification were measured using Entropy index, while International Diversification was measured using proportion of export sales over total sales. Efficiency was measured using Data Envelopment Analysis – BCC Model using total assets as input variable and return on asset, return on equity, profit margin, earning per share, market to book value and Tobin’s Q as output variables. This research also uses five control variables which are firm’s size, leverage, firm’s age, liquidity, and exchange rate. This research use manufacture companies listed in Bursa Efek Indonesia in 2013-2016 as research samples. The result of this research show Related Diversification gives negative effect on Efficiency, Unrelated Diversification gives positive effect to Efficiency, and no significant effect from International Diversification to Efficiency. The implication from this research indicates that Unrelated Diversification strategy is better for manufacturing firms in Indonesia and Efficiency will decrease as firm’s size grow. Keywords: Efficiency, International Diversification, Related Diversification, Unrelated Diversification https://doi.org/10.21632/saki.2.2.149-176